Racism, identity and displacement in selected Canadian ethnic fictions by Lawrence Hill and M. G. Vassanji - Abbas, Hussein Ali (2019)
This study addresses the issue of the representation of the marginalised minorities in literary texts by immigrant authors in White-dominated Canada. It examines six selected novels, which are Some Great Thing (1992), Any Known Blood (1997) and The Book of Negroes (2007) by Lawrence Hill, and No New Land (1991), The In- Between World of Vikram Lall (2003), and The Magic of Saida (2012) by M. G. Vassanji. In No New Land, Vassanji’s newly-arrived immigrant character Nurdin has to live in poverty as he is not given a job because he has no ‘Canadian experience’, whereas Hill’s Aminata in The Book of Negroes is given no chance to live among the Whites in the town she works in because she is Black. In Vassanji’s The Magic of Saida, Kamal Punja, who is born to a mixed family, suffers from an identity crisis because Canada does not recognise the identity of biracial immigrants. In Vassanji’s The In-Between World of Vikram Lall, Vic is trapped between the oriental native world devastated by war and the occidental host, which is flourishing in peace. In Hill’s Some Great Thing, Yoyo is forced by the long harshly cold winter of Canada to return to his sunny homeland in Cameroon, while Cane V’s sense of identity loss in Hill’s Any Known Blood compels him to go to Africa and the USA to unearth the roots of his family. In terms of theory, this study uses the ideas of both Critical Multiculturalism and Post-Colonialism to address the main concepts and their relevant themes of these novels. Frantz Fanon and Edward Said’s ideas on racism are used to examine racism-caused poverty and the segregation of immigrants. Homi Bhabha and Sneja Gunew’s ideas on immigrants’ hybrid identity are used to address biracial immigrants’ identity crises and bicultural in-betweenness. Displacement, voluntary or compulsory, is investigated respectively through the themes of longing/belonging and the search for familial roots, dependent on John McLeod and Neil Bissoondath’s ideas on immigrants’ return home and immigrants’ family roots. This study has three objectives to attain. The first is to explore how the African and South Asian immigrant characters are affected by racism in multicultural Canada. The second is to investigate the reasons and results of identity problems that are imposed on the immigrant characters of these two groups in that country. The third is to examine the reasons which trigger the sense of displacement among the immigrant characters of these two minorities in that host country. As this study finds that African and South Asian immigrant characters of the selected fictional texts suffered in terms of racism, identity, and displacement, it is concluded that literature contributes to give representation to those non-Europeans who have remained voiceless for many decades in Canada. In the end, this study recommends that more studies need to be done on literary texts by immigrant authors to investigate the stories of minority characters other than those of African and South Asian origin.